2011
DOI: 10.1248/bpb.34.1596
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Protection with Danshensu in Spontaneously Hypertensive Rats

Abstract: The objective of the present study was to evaluate the cardiovascular protective effects of Danshensu, a water-soluble active component of Danshen, in spontaneously hypertensive rats (SHR). SHR (male, 9 weeks old, n‫؍‬ ‫)03؍‬ were divided into three groups: 1) saline control (n‫؍‬ ‫;)01؍‬ 2) a Danshensu (10 mg/kg/d, intraperitoneally (i.p.)) treatment group (n‫؍‬ ‫;)01؍‬ and 3) a Valsartan (10 mg/kg/d, intragastrically (i.g.)) treatment group (n‫؍‬ ‫.)01؍‬ Age-matched Wistar-Kyoto rats (n‫؍‬ ‫)01؍‬ were used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Using spontaneously hypertensive rats, Tang et al found that administration of Danshensu (10 mg/kg/d for 6 weeks) decreased blood pressure and inhibited arrhythmias via increasing serum nitric oxide (NO) content and nitric oxide synthase activity [74]. Using isoproterenol (2.5 mg/kg/d for 7 days, s.c.) induced myocardial hypertrophy rats, Danshensu treatment (3 and 10 mg/kg/d from day 4 to 7 of isoproterenol treatment, i.p.)…”
Section: Effects Of S Miltiorrhiza and Its Isolated Compounds On Thementioning
confidence: 99%
See 1 more Smart Citation
“…Using spontaneously hypertensive rats, Tang et al found that administration of Danshensu (10 mg/kg/d for 6 weeks) decreased blood pressure and inhibited arrhythmias via increasing serum nitric oxide (NO) content and nitric oxide synthase activity [74]. Using isoproterenol (2.5 mg/kg/d for 7 days, s.c.) induced myocardial hypertrophy rats, Danshensu treatment (3 and 10 mg/kg/d from day 4 to 7 of isoproterenol treatment, i.p.)…”
Section: Effects Of S Miltiorrhiza and Its Isolated Compounds On Thementioning
confidence: 99%
“…Using primary mesenteric vascular smooth muscle cells isolated from spontaneously hypertensive rats, Danshensu treatment enhanced the K + and Ca 2+ activated K + channel current density when the test potential was set at +60 mV [74]. Ca 2+ -activated K + (K Ca ) channels along with K + (K V ) channels play an important role in regulating vascular tone and blood pressure [138].…”
Section: Effects Of S Miltiorrhiza and Its Isolated Compounds On Thementioning
confidence: 99%
“…Danshensu (10 mg/kg/day i.p.) decreased the HW/BW index, prevented the increase of blood pressure, and reduced arrhythmias in rats exposed to I/R [188]. In addition, danshensu possessed a cardioprotective effect against I/R injury when given to rats during reperfusion (30 and 60 mg/kg, for 3 h) [108].…”
Section: In Vivo Effects Of Polyphenols Against Oxidative Stress-imentioning
confidence: 99%
“…The water extract of SM that contains lithospermic acid B (also named tanshinoate B) and Sal B exhibits an antihypertensive effect through the inhibition of angiotensin-converting enzyme or the renin angiotensin system [6265]. Sal B and danshensu, the major hydrophilic constituents of SM, can regulate vascular tone and reduce blood pressure by activating of the calcium-activated big potassium (BK CA ) channel [66, 67]. In addition, SM injection can decrease plasma levels of endothelin-1 and thromboxane B2 [68].…”
Section: Resultsmentioning
confidence: 99%